Split Thickness Skin Graft Pada Pasien Abses Submandibula Dengan Ulkus Regio Colli Dextra - Aditomo, Rano; Yusmawan, Willy (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Skin graft is a surgical procedure in which part or all of the thickness of the skin is removed from a region of origin (donor) without being accompanied by vascularity to another area (recipient) to cover a defect. Indication of skin graft performed on primary non-sealable wounds. The purpose of writing this case report is to report one case of a patient who was split thickness skin graft (STSG) and provide knowledge to colleagues on how to do it considering the very rare cases in ORL-HNS department. This article reported a 61-year-old male with complaints of a reddish open wound on the right neck and diagnosed with necrosis of the colli dextra region due to a submandibular abscess. Patients are carried out management of wound tissue closure with STSG technique, with good treatment the grafting results can be successful without complications after the patient controls 1 month post-STSG and no secondary infection is obtained at 6 months post-STSG.